Analisis Yuridis Disparitas terhadap Putusan Pengadilan Tindak Pidana Penyalagunaan Narkotika dengan Barang Bukti yang Melebihi Penyalahgunaanya : (Studi Putusan Pengadilan Negeri Karawang) - Hanna Zahra Maharani Hilman; Muhammad Gary Gagarin Akbar; Muhamad Abas (CV Rewang Rencang, 2025)
In Indonesia, drug abuse and distribution are still serious problems. The absence of a threshold for drug possession for abusers causes ambiguity in law enforcement. This study analyzes the regulation of the threshold for drug possession for drug abusers as seen from two Karawang District Court Decisions used as comparative references so that there is a disparity in decisions reviewed from evidence that exceeds its abuse. Evidence can be used as a reference to determine whether the goods exceed the personal consumption limit. This study uses a normative legal approach by analyzing qualitatively, the results show that there is a lack of guidelines on the threshold for possession. Judges' interpretations often affect evidence, and inconsistent guidelines lead to differences in sentences.